Patient safety as part of a health care quality system on Polish and Swedish example Principles of therapeutic contact: physician-patient - Dąbrowska-Bender, Marta; Steć, Monika (Polish Journal of Public Health, 2009)
The present study is an  attempt to show the aspect of patients safety in Polish and Swedish healthcare system, the respect for their rights and  providing them with medical services on the highest level through, inter alia, free access to healthcare, decent conditions of stay in treatment, adequate information and responsibility on the part of highly qualified medical staff. Patient safety covers a wide range of actions and is one of the priorities for quality healthcare. The direct impact on patient safety is exerted by regulations, financial situation, quality standards of health  professionals, infrastructure, equipment and medical technologies. This applies both to hospital, health center, care home, hospice care or other places where medical assistance is provided. Swedish healthcare system is one of the best performing systems among highly  developed countries. Its activity and organizational structure might be pattern for changes to improve the Polish healthcare system.